Fourier transform infrared (FT-IR) spectroscopic investigations of four agarophytes from northern Arabian sea (Bangladesh Journal of Botany, 2019)
The fresh specimens of Champia compressa Harvey, Gelidium usmanghanii Afaq-Husain and M. Shameel, Gracilaria foliifera (Forsskål) Børgesen and Hypnea musciformis (Wulfen) J. V. Lamouroux, were collected from the coastal areas of Karachi (Pakistan) and their yield of agar was observed. With preextraction technique the percentage of algal yield was found to range from 13 to 28%. High quality gel strength was determined by modulus of elasticity i.e. (550 – 612g/cm2) and 1090 kPa and extraction time was 2 hrs. The structure of agar and agar contents were investigated by FT-IR spectroscopy for the first time from Pakistan. The results revealed some interesting characters (non sulphated β-D galacto pyranose residues, 3,6 anhydro galactose vibration), which were not reported earlier.